Financial Literacy Learning in Indonesian Children Literature - Hayati, Yenni; Putri, Diantri Seprina; Lubis, Prinsella Balqis (Talenta Publisher, 2024)
At least there are six literacy skills that must be owned by humans. They are language, science, mathematics, finance, digital, and citizenship literacy. These six kinds of literacy must be learned since the early childhood. Therefore, literacy learning should be taught in communicative and fun ways. As a result, appropriate teaching medias that can meet these requirements are needed. Children literature appears as one of these medias that contains literacy learning in it. One of the most crucial literacy skills that should be learned by humans is financial literacy since it relates to the knowledge and ability in applying the understanding of concepts, risks, skills, and motivations in the context of financial. Data related to financial literacy learning were found in every genre of children literature such as children proses, rhymes, or dramas. The data used on this study were collected from ten children's proses in the form of children's novel, ten nursery rhymes including children's song verses, and three children's dramas. The learning of financial literacy found in children literature were seen in verses and lines of rhymes, events in proses, and dialogues in children's dramas.